Le développement de l'idée des droits de l'homme: les tensions contradictoires et les compromis concevables - del Campo, Julio (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
The main conflicts and antagonisms presently plaguing the world are the conflicting interpretations as to the substance of what constitutes human rights. According to the author, the conflict must be recognized instead of hidden under a list of additional rights which serve only to add heterogeneous requirements. This process is essential and a prerequisite to the search for a rational compromise.